PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATERI IMAN KEPADA KITAB ALLAH MELALUI MEDIA MICROSOFT POWERPOINT DI SMP NEGERI 2 DEMAK - Hanik Rasidah (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study was to increase motivation and learning outcomes of the material of Faith in the Books of Allah through microsoft powerpoint media for 32 students of class VIII-F SMP Negeri 2 Demak semester I of the 2019/2020 academic year. This research is a classroom action research. Sources of data consist of qualitative data in the form of observation sheets, daily notes, and photos of learning documentation, and quantitative data sources in the form of written tests. The data was collected using non-test techniques for qualitative data, and test techniques for quantitative data by comparing the observed data with the pre-test and post-test results given to students. This research was conducted in two cycles, and each cycle through four stages, namely planning, action, observation, and reflection. The results showed that the microsoft powerpoint media can increase student motivation from cycle I to cycle II has increased from 72.78% in the enough category to 91.91% in the good category or an increase of 19%. The learning outcomes of the knowledge aspect in the first cycle of students who completed classically were 68.75%, and in the second cycle it became 93.75% or from 22 students to 30 students, so there was an increase in students’ classical completeness from cycle I to cycle II by 25%.